2004
DOI: 10.1007/s00246-003-0483-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Neo-Aortic Root Enlargement and Aortic Regurgitation Following Arterial Switch Operation

Abstract: The objectives of this study were to evaluate changes in dimension of the neo-aortic annulus, aortic root, and aortic anastomosis following arterial switch operation (ASO) and to identify risk factors for developing abnormal neo-aortic root enlargement and aortic regurgitation (AR). Prior studies report development of neo-aortic root dilatation and AR in a small subset of patients after ASO. Predisposing factors for neo-aortic root dilatation and development of moderate/severe AR are poorly understood. We perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
4
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 18 publications
6
75
4
1
Order By: Relevance
“…Aortic root enlargement after ASO has previously been reported from our group 4 and by other echocardiographic studies. 19,20 A CMR study by Grotenhuis et al 8 in 15 TGA patients also revealed significantly increased aortic root diameters. Furthermore, they showed that patients with AR had even larger aortic root diameters.…”
Section: Aortic Dimensions and Aortic Insufficiencymentioning
confidence: 92%
“…Aortic root enlargement after ASO has previously been reported from our group 4 and by other echocardiographic studies. 19,20 A CMR study by Grotenhuis et al 8 in 15 TGA patients also revealed significantly increased aortic root diameters. Furthermore, they showed that patients with AR had even larger aortic root diameters.…”
Section: Aortic Dimensions and Aortic Insufficiencymentioning
confidence: 92%
“…Progressive dilatation and valvar insufficiency of the reconstructed aortic root may be problematic and may necessitate valve replacement later in life. 35 Branch pulmonary artery stenosis may result from pulling the main pulmonary artery trunk forward to anastomose it to the former aortic root. 36 This may be a clinically important afterload for the RV or may significantly redistribute pulmonary blood flow from 1 lung to the other if the degree of obstruction of the branches is unequal.…”
Section: Sommer Et Almentioning
confidence: 99%
“…Neoaortic regurgitation is a concern, and is present to some degree in the majority of adult patients [19••]. In young adults with ASO, an up to 3% incidence of moderate-severe neoaortic regurgitation has been reported [62,63]. Neoaortic regurgitation is related to root dilatation and to the need for pulmonary artery banding prior to definitive repair or repair of an associated VSD [61,62,64,65].…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%